The Scelidotheriine Proscelidodon (Xenarthra: Mylodontidae) from the Late Miocene of Maimará (Northwestern Argentina) - Pujos, François Roger Francis (2012)
Xenarthra constitutes one of the most peculiar clades of the South American mammalian fauna and includes sloths (Tardigrada), anteaters (Vermilingua), and armored xenarthrans (Cingulata). Its phylogenetic affinities among placental mammals and their origins remain doubtful (Asher and Helgen, 2010). Xenarthrans first appear in the Itaboraian age (late Paleocene?early Eocene; Oliveira and Goin, 2011) represented by the Dasypodidae in the locality of Itaboraí, Brazil. Sloths are first recorded from the early Oligocene (Tinguirirican age) of Chile and became abundant during the late Oligocene (Deseadan age), mainly in Argentina and Bolivia with representation of Mylodontidae and Megalonychidae (Pujos et al., 2012).